(untitled) (Research, Society and Development, 2022)
The study sought to comparatively analyze two soil analyzes, a soil sample from a plot of land that is in a vegetable production system, with a non-certified agroecological base, in operation for approximately 4 years, and the other soil sample from the same glebe but in the form of a control containing only a soil correction with calcite limestone. Physical and chemical aspects were analyzed through soil analysis. The data were cataloged, analyzed and compared. The evolution of the chemical levels of the soil analysis was based on the analysis of the organic com-post used in the form of fertilization. It was identified that there is an increase in al-most all macro and micronutrients present in the analysis, with emphasis on phosphorus and potassium. Only one micronutrient, manganese, showed a decrease in the index available in the soil.